Cannulation strategy for centrifugal-flow ventricular assist device implantation late after arterial switch operation. (24th October 2017) - Beckerman, Ziv; Tunuguntla, Hari; Fraser, Charles D; Adachi, Iki
Abstract: The field of paediatric ventricular assist device (VAD) support is growing rapidly. Among paediatric patients, those with complex congenital heart disease represent a challenging population for VAD support. This report describes a patient with a remote history of an arterial switch operation for d -transposition of the great arteries who developed ischaemic cardiomyopathy necessitating centrifugal-flow VAD support as a bridge to cardiac transplantation. Because of the unique anatomy and the complicated vascular situation, implantation of the centrifugal-flow VAD and subsequent explantation for cardiac transplantation required modifications to the standard surgical approach. The details of surgical pitfalls encountered are described.